Effect of a tailored assistive technology intervention on older adults and their family caregiver: a pragmatic study protocol. Issue 1 (December 2016) - Demers, Louise; Mortenson, W.; Fuhrer, Marcus; Jutai, Jeffrey; Plante, Michelle; Mah, Jasmine; DeRuyter, Frank
Abstract Background Many older adults with mobility limitations use assistive technology to help them perform daily activities. However, little attention has been paid to the impact on their family caregivers. This neglect produces an incomplete portrayal of the outcomes of assistive technology provision. This paper describes the protocol for a study that examines the impact of a tailored assistive technology intervention that is inclusive of assistance users and their family caregivers. Methods/design This research will use a combination of quantitative and qualitative methods. The quantitative portion will be an experimental, single-blinded study in which participants are randomly assigned to either an experimental assistive technology intervention or a standard care group. We will enroll 240 participants (120 dyads) into the study from three Canadian sites. Participants will include older adults (>55) and family caregivers who provide ≥4 h per week of assistance with daily activities and social participation. The primary outcome measure for the older adults will be the Functional Autonomy Measurement System, and the primary outcome measure for the caregivers will be the Caregiver Assistive Technology Outcomes Measure. Qualitative data will be collected through detailed records of the therapists' interventions, as well as through interviews with dyads and therapists following the interventions. Data collection will occur at baseline (T0 ) with follow-ups at 6 weeks (T1 ), 22 weeks (T2 ), and 58 weeks (T3 ) after baseline evaluation. Discussion The findings from this study will help service providers and clinicians to move forward with assistive technology recommendations that are more attuned to the needs of both older adults with mobility limitations and their family caregivers. Additionally, the study's findings will enhance our conceptual understanding of the spectrum of assistive technology outcomes and set the stage for econometric studies assessing cost-effectiveness. Trial registration ClinicalTrials.gov Identifier:NCT01640470 . Registered 11/21/2011.